2002
DOI: 10.1088/0953-4075/35/12/306
|View full text |Cite
|
Sign up to set email alerts
|

Negative photoion spectroscopy of SF6 in the inner valence and S 2p energy regions

Abstract: Negative fragment ion formation from SF6 has been studied using synchrotron radiation within the energy range 20-205 eV. The fragment ions F-, F2-, S- and SF- have been observed. It is shown that shape resonance and unoccupied valence orbitals play an important role in negative ion formation after photoexcitation of inner valence and S 2p electrons. The negative ion yields after photoexcitation of a S 2p core electron show evidence of localization of the shape resonance orbitals around the central S ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…F -and CF 4 into CF 3 + ? F -has been studied previously by Mitsuke et al [21,22] and Scully et al [23]. The results presented here have seen a much larger number of anions than observed by these groups, and the data of Mitsuke et al has allowed the SF 5 CF 3 data to be put on an absolute scale (as outlined in Sect.…”
Section: Background Informationsupporting
confidence: 61%
“…F -and CF 4 into CF 3 + ? F -has been studied previously by Mitsuke et al [21,22] and Scully et al [23]. The results presented here have seen a much larger number of anions than observed by these groups, and the data of Mitsuke et al has allowed the SF 5 CF 3 data to be put on an absolute scale (as outlined in Sect.…”
Section: Background Informationsupporting
confidence: 61%
“…21,22 Based on Frank-Condon arguments, the latter process is thought to be more common, although significant coupling between Rydberg and ion pair states is a requirement − one which is not always met. 24,25 and Scully et al 26 We have seen a much larger number of anions than observed by these groups, and the data of Mitsuke et al 24,25 has allowed us to put our SF 5 CF 3 data on an absolute scale. To our knowledge this is the first report of ion pair production following VUV photoexcitation of SF 5 CF 3 .…”
Section: Introductionmentioning
confidence: 60%
“…Finally, it is noted that shape resonances have been observed in the 19 yields of many anions in both SF 6 and CF 4 above 25 eV. 26,31 There is no obvious evidence for such peaks in our ion yields from SF 5 CF 3 , but it would be surprising if they were not present.…”
Section: II Yield Of Sfmentioning
confidence: 81%
“…These data are available in the literature for CF 4 [41], SF 6 [42,43], CH 4 [44], CH 3 X (X = F, Cl, Br) [45], C 2 H 4 [46], C 2 H 6 [47,48], C 3 H 8 [47], and the chlorofluoromethanes (CFCl 3 , CF 2 Cl 2 , CF 3 Cl) [49]. The present work is in excellent agreement with these earlier studies and in most cases the quality and quantity of data obtained have improved.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Results have shown that in most cases, if charge transfer is energetically allowed, it will occur and is usually the dominant reaction channel [34][35][36][37][38][39][40][41][42][43][44][45]. The same experiments have shown that some cations and molecules do not react when the energetics do not allow for charge transfer.…”
Section: Cation-molecule Reactionsmentioning
confidence: 99%